Surface roughness average and scanning electron microscopic observations of resin luting agents Alteração de rugosidade superficial e observações em microscopia eletrônica de varredura de cimentos resinosos - Rafael Francisco Lia Mondelli; Anuradha Prakki; Renato Cilli; Maria Fidela de Lima Navarro; José Mondelli (Journal of Applied Oral Science, 2003)
The objective of this work was to evaluate the surface roughness changes of three current resin cements after tooth brushing simulation, as well as discuss its relation with scanning electron microscopic observations. The materials employed were Enforce Sure Cure (Dentsply), Rely X (3M-ESPE) and Variolink II (Vivadent). They were subjected to brushing abrasion (100,000 strokes for each specimen) and the surface roughness alterations (before and after strokes) were detected. For each roughness test condition, specimens were coated with gold-palladium and observed on a DSM 900 Zeiss scanning electron microscope. Roughness changes values (Ra) were statistically increased after brushing strokes. Based on the microscopic observations and roughness changes analysis, all cements studied became rougher after brushing strokes. O objetivo desse estudo foi avaliar a alteração de rugosidade superficial de três cimentos resinosos após submetê-los a ciclos de escovação simulada e analisar qualitativamente a sua superfície através de observações microscópicas. Os materiais empregados neste estudo foram Enforce Sure Cure (Dentsply), Rely X (3M-ESPE) e Variolink II (Vivadent). Estes foram submetidos à ciclos de escovação simulada (100.000 ciclos para cada espécime) e a alteração de sua rugosidade superficial (antes e após escovação) foi avaliada. Para cada material e condição de rugosidade, espécimes foram selecionados, metalizados e observados em microscopia eletrônica de varredura (DSM 900 Zeiss). Baseado nas observações microscópicas e nos valores de alteração de rugosidade, todos os materiais apresentaram aumento de rugosidade aritmética (Ra) após ciclos de escovação simulada.